1991
DOI: 10.1203/00006450-199106010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Metabolites Produce Pulmonary Vasoconstriction in Young Pigs

Abstract: ABSTRACT. Reactive oxygen metabolites appear to modulate pulmonary vascular changes. To study the effects of free radical formation in vivo, we investigated five groups of young pigs by recording hemodynamic changes after xanthine oxidase infusion alone and after pretreatment with hypoxanthine or possible blocking agents. The pulmonary vascular pressure increased rapidly in the groups without inhibition reaching maximum levels 25 min after the start of the experiment. The pulmonary artery blood flow declined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 21 publications
1
25
1
Order By: Relevance
“…Intestinal I/R leads to pulmonary vasomotor dysfunction, with an imbalance of vascular smooth muscle contraction and relaxation [33], and pulmonary upregulation of the potent vasoconstrictor thromboxane A 2 , TXA 2 [34]. It has been suggested that oxygen radicals play a role in these events [35, 36], a finding that is supported by the fact that NAC pretreatment in patients undergoing operation for abdominal aortic aneurysm prevented against the increase in plasma lipid peroxide levels, thromboxane, and prostacyclin levels seen in patients not receiving pretreatment [32]. Based on these reports and our findings on the effectiveness of treatment with NAC, it is thus possible that reactive oxygen species are involved in mediating the decrease in pulmonary blood content seen after intestinal I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal I/R leads to pulmonary vasomotor dysfunction, with an imbalance of vascular smooth muscle contraction and relaxation [33], and pulmonary upregulation of the potent vasoconstrictor thromboxane A 2 , TXA 2 [34]. It has been suggested that oxygen radicals play a role in these events [35, 36], a finding that is supported by the fact that NAC pretreatment in patients undergoing operation for abdominal aortic aneurysm prevented against the increase in plasma lipid peroxide levels, thromboxane, and prostacyclin levels seen in patients not receiving pretreatment [32]. Based on these reports and our findings on the effectiveness of treatment with NAC, it is thus possible that reactive oxygen species are involved in mediating the decrease in pulmonary blood content seen after intestinal I/R.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary vessels are continually exposed to free radicals and reactive oxygen species originating from inspired air or inflammatory cells, and pulmonary vascular tone is dramatically altered by reactive oxygen species such as O 2 ⅐Ϫ (3,4). At birth, the newborn encounters a much more oxygen-enriched world than the relatively hypoxic fetus.…”
mentioning
confidence: 99%
“…Perfusion of XO (or with hypoxanthine) to isolated rat lungs increased pulmonary artery pressure (PAP) and vascular resistance (PVR) [8]. Similarly, previous in vivo studies from our group demonstrated that infusion of XO induced a significant pulmonary vasoconstriction in young pigs (8 weeks old) [7,9]. Its effects on the neonatal pulmonary hemodynamics, however, have not been investigated.…”
Section: Introductionmentioning
confidence: 80%
“…Tate et al [5] and Sanderud et al [7,10] reported that the activation of cyclooxygenase subsequent with releasing thromboxane might account for its mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation